Climatology of long‐range transported Asian dust along the West Coast of the United States. Issue 21 (4th November 2014) - Creamean, Jessie M.; Spackman, J. Ryan; Davis, Sean M.; White, Allen B.
Abstract: The contribution of trans‐Pacific dust estimated from satellite observations has been shown to be 3 times greater than domestic dust in North America throughout the year. Thus, a quantitative understanding of the frequency and locations where Asian dust is transported is necessary to improve global dust modeling for weather and climate predictions. This work presents a 10 year record (2002–2011) of dust along the U.S. West Coast estimated from the Interagency Monitoring of Protected Visual Environments network in an effort to characterize the seasonal cycle and interannual variability of Asian dust transport. In addition, observations of dust exported from East Asia were analyzed along with air mass trajectories and satellite and ground‐based precipitation data to investigate seasonal variability of Asian dust transport. On average, Asian dust concentrations (0.08–0.60 µg m −3 ) from ground‐based observations were 1.7 times those of local dust (0.00–0.53 µg m −3 ) and 23% (up to 44%) of fine particulate matter (particles with diameters ≤ 2.5 micrometers, or PM2.5 ) mass concentrations at high elevations in the spring. The maximum in springtime Asian dust on the U.S. West Coast was attributed to higher source concentrations (10.98–36.27 µg m −3 ) and reduced potential for wet removal over the Pacific Ocean and U.S. West Coast. Although trans‐Pacific transport was more favorable during the winter, minimum concentrations of Asian dust were observed on the U.S. West Coast (0.11 µg m −3 ) due to a lower source influence and higher potential for wet removal during transport. Multiobservational approaches such as these should be taken into account when modeling transport of Asian dust to the western U.S. Key Points: A 10 year Asian dust record is presented on the U.S. West Coast Seasonal variability of transported Asian dust can be explained by wet removal